Canopy deposition characteristics of different orchard pesticide dose models - Zhou, Qingqing; Xue, Xinyu; Chen, Chen; Cai, Chen; Jiao, Yuxuan (International Journal of Agricultural and Biological Engineering, 2023)
Pesticide dose model based on canopy characteristics is the guidance basis for spray parameters adjustment. In this study, the calculation formula and canopy deposition characteristics of leaf wall area (LWA) model, tree row volume (TRV) model, and optimal coverage method (OCM) model were described and compared. A tower air-assisted spray test bench was applied to provide fine quality droplets, suitable wind speed and demand spray flow rate for corresponding models, an electric flat board vehicle was applied to drive tree in a straight line to simulate the sprayer movement speed, and droplet deposition distribution were tested in different leaf area density canopy. The results showed that the spray flow rates of three pesticide dose models decreased gradually. LWA model was only related to canopy height, TRV model was related to canopy height and canopy diameter, while OCM model was related to canopy height, canopy diameter and leaf area density. Whether dense or sparse canopy, TRV model basically satisfied the requirement of coverage rate greater than 33% in the entire canopy, OCM model met the requirement of coverage density greater than 70 droplets/cm2. However, LWA model, for dense canopy, unit area deposition of outermost leaves near sprayer was 3.6 times of the apple leaf maximum retention, which had a high loss risk; for sparse canopy, penetration rates of outermost leaves far away sprayer, that is, the drift rate was 21.4%. The discussion leads to the conclusion that for conventional spraying, TRV model represented a substantial improvement compared to LWA model, and OCM model was a reasonable low volume spraying model. This study provides a reference to different growth seasons spray amount adjustments in orchard.Keywords: orchard plant protection, pesticide dose model, leaf wall area, tree row volume, optimal coverage methodDOI: 10.25165/j.ijabe.20231603.7665Citation: Zhou Q Q, Xue X Y, Chen C, Cai C, Jiao Y X. Canopy deposition characteristics of different orchard pesticide dose models. Int J Agric & Biol Eng, 2023; 16(3): 1–6.